Cable bacteria promote DNRA through iron sulfide dissolution - Adam J. Kessler; Michaela Wawryk; Ugo Marzocchi; Keryn L. Roberts; Wei Wen Wong; Nils Risgaard‐Petersen; Filip J. R. Meysman; Ronnie N. Glud; Perran L. M. Cook (Limnology and Oceanography, 2019)
Cable bacteria represent a newly discovered group of filamentous microorganisms, which are capable of spatially separating the oxidative and reductive half‐reactions of their sulfide‐oxidizing metabolisms over centimeter distances. We investigated three ways that cable bacteria might interact with the nitrogen (N) cycle: (1) by reducing nitrate through denitrification or dissimilatory nitrate reduction to ammonium (DNRA) within their cathodic cells; (2) by nitrifying ammonium within their anodic cells; and (3) by indirectly affecting denitrification and/or DNRA by changing the Fe 2+ concentration in the surrounding sediment. We performed 15 N labeling laboratory experiments to measure these three processes using cable bacteria containing sediments from the Yarra River, Australia, and from Vilhelmsborg Sø, Denmark. Our results revealed that in the targeted systems, cable bacteria themselves did not perform significant rates of denitrification, DNRA, or nitrification. However, cable bacteria exhibited an important indirect effect, whereby they increased the Fe 2+ pool through iron sulfide dissolution. This elevated availability of Fe 2+ significantly increased DNRA and in some cases decreased denitrification. Thus, cable bacteria presence may affect the relative importance of DNRA in sediments and thus the extent by which bioavailable nitrogen is lost from the system.